ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PERATAAN LABA (Studi Pada Perusahaan Sektor Non Keuangan dan Perbankan yang Go Public di BEi tahun 2004 sampai dengan tahun 2008) - Khasana, Etista Widya (JURNAL BISNIS STRATEGI, 2011)
The practice of income smoothing is a common phenomenon that occurs as a management effort to reduce fluctuations in reported earnings.  This action causes the disclosure of information on income earnings to be misleading. This shows that the profit is something that most considered by investors to make a decision whether to invest or not. The purpose of this study was to analyze the influence of independent variables is profitability, devidend payout ratio, firm size, leverage and ownership structure by the public against the income smoothing the company went public in non financial and banking sector in Indonesia Stock Exchange (IDX).The problem in this research is the tendency of a stable income and tend to increase and the gap between  a researcher with the other studies. Period in this study was in 2004 until 2008. The sample size taken in this study were 16 companies went public on nonfinancial and banking sector in Indonesia Stock Exchange (IDX) by using purposive sampling method. Tools of analysis used logistic regression test.The result is not proven profitability significantly and negatively related to income smoothing. Parliament and the size of the company proved to have positive and significant impact on income smoothing. Leverage is not proven to have positive and significant impact on the income smooth ing. Ownership of shares by the public proved significantly and negatively related to income smooth ing. Large variations in the income smoothing which can be explained by variations in the variable return on assets (ROA), the dividend payout ratio (DPR), size (size), debt to equity ratio (DER) and public shareholding of 32.3 percent, while the remaining amount 67. 7 percent who are not influ enced by other variables studied